Antibacterial activity of selected siddha herbo-mineral preparations against clinically isolated enterococcus species - K.L, shobha K.L; K.L, Shobha; S.J, Akshatha; Shenoy, Revathi; L, Ramachandra; L, Bernitis (International Journal of Pharmacology and Toxicology, 2014)
Objective: In siddha medicinal practice the use of plant extracts as well as inorganic natural preparations has a vital role as medicines. The present research in the field of phytomedicine is to evaluate the antibacterial properties of three herbo- mineral siddha drugs (Palakarai parpam, Padikara parpam, Uppu chenduram) on clinically isolated Enterococcus strains. Materials and Methods: Fifteen bacterial strains isolated from clinical samples were identified as Enterococcus faecalis(7), E. faecieum(8).The susceptibility of the microorganisms to the  siddha drugs (Palakarai parpam, Padikara parpam, Uppu chendooram) were screened by disc diffusion method and the effective drug’s MIC value was calculated by agar dilution method. Results: Padikara parpam was considered sensitive against the tested Enterococcus faecalis and Enterococcus faecium .Agar dilution was performed with 1%, 0.5%, 0.25% and 0.12% of the drug dilution. MIC was found to be 0.5%. Conclusion: The drug Padikara parpam contains essential elements which are considered to be good anti-microbial activity against Enterococcus spp. To conclude, the claim in the siddha system of medicine is scientifically validated.   Keywords: Palakarai Parpam, Padikara Parpam, Uppu Chendooram, Siddha Medicine, Antibacterial Activity, Enterococcus species.